2013
DOI: 10.1007/s11552-012-9483-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Diagnosis and Wide-Awake Surgical Treatment of Proximal Median Nerve Entrapment at the Elbow: A Prospective Study

Abstract: Background Proximal median nerve entrapment (PMNE, or pronator syndrome) at the elbow has traditionally been considered an elusive and rare diagnosis, as it is seldom detectable using electrophysiological techniques. In this paper, the clinical manifestations, physical diagnosis, surgical technique, and results of surgical treatment of PMNE are presented, with accompanying instructional video. Patients/Methods During 2011, 44 patients with PMNE were surgically released and followed prospectively, 22 women/22 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
65
0
9

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(76 citation statements)
references
References 18 publications
2
65
0
9
Order By: Relevance
“…Distal entrapment in the ulnar tunnel is less well described, but in our experience it is not uncommon, and decompression is the standard surgical procedure 26 . As per the recent paper by Hagert on wide awake treatment of (occult) proximal median nerve entrapment 27 : it is our experience that distal ulnar nerve entrapment may similarly be overlooked and is not usually detected on nerve conduction studies. Moreover, in the present series all the three cases of ulnar tunnel syndrome had a false negative nerve conduction study result for ulnar tunnel entrapment; and this has confounded the diagnosis of their clinically obvious ulnar tunnel syndromes.…”
Section: Discussionmentioning
confidence: 78%
“…Distal entrapment in the ulnar tunnel is less well described, but in our experience it is not uncommon, and decompression is the standard surgical procedure 26 . As per the recent paper by Hagert on wide awake treatment of (occult) proximal median nerve entrapment 27 : it is our experience that distal ulnar nerve entrapment may similarly be overlooked and is not usually detected on nerve conduction studies. Moreover, in the present series all the three cases of ulnar tunnel syndrome had a false negative nerve conduction study result for ulnar tunnel entrapment; and this has confounded the diagnosis of their clinically obvious ulnar tunnel syndromes.…”
Section: Discussionmentioning
confidence: 78%
“…We have since this first patient experienced similar positive scratch collapse test in two additional patients. The patho-physiology is similar to the carpal tunnel syndrome and similar nerve entrapment on the arm [6]. Brown et al found that the scratch collapse test was a seemingly reliable physical examination technique for localizing the point of maximal nerve compression in patients with cubital tunnel syndrome [7].…”
Section: Discussionmentioning
confidence: 99%
“…In the cubital fossa, the median nerve may be entrapped by a thickened lacertus fibrosus (Hagert 2013) or accessory tendons of the biceps brachii (Spinner et al 1991).…”
Section: Variations Causing Median Nerve Entrapmentmentioning
confidence: 99%